Collaborative Governance on Handling Stunting in West Java Province of Indonesia - Mediyana Sofyan, Meti; Fauziyah, Ghina; Rahardian, Ramaditya (Indonesian Association for Public Administration (IAPA), 2024)
Stunting prevention is still one of the main concerns of the Central Government and Regional Governments from time to time, because the stunting prevalence rate in West Java is still above the average stunting prevalence in Indonesia. So then there needs to be innovation and collaboration from various stakeholders to overcome the current stunting problem. This research seeks to analyze solutions in preventing and handling people who are indicated to be stunted with the Collaborative Governance approach, this approach so that it becomes one of the new breakthroughs that can then be adopted and implemented. The research method approach used in this research is qualitative with data collection in the form of interviews and documentation studies. The results of the study show that various actors are involved in handling the problem of stunting in West Java with existing collaboration, starting from building communication with face-to-face dialogue, shared understanding, and commitment to the process.